2015
DOI: 10.17245/jdapm.2015.15.3.113
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mandibular skeletal characteristics on inferior alveolar nerve block anesthesia

Abstract: BackgroundThe inferior alveolar nerve block (IANB) is the most common anesthetic techniques in dentistry; however, its success rate is low. The purpose of this study was to determine the correlation between IANB failure and mandibular skeletal characteristicsMethodsIn total, 693 cases of lower third molar extraction (n = 575 patients) were examined in this study. The ratio of the condylar and coronoid distances from the mandibular foramen (condyle-coronoid ratio [CC ratio]) was calculated, and the mandibular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…For successful IANB, extraoral landmarks, such as degree of ramal flaring and height and width of the mandibular ramus as well as intraoral landmarks should be considered [1740]. You et al reported that the IANB failure rates were significantly higher in the retrognathic mandible (14.5%) than in the normal mandible (7.3%) and prognathic mandible (9.5%) [41]. It is because the distance from the mandibular foramen to the condylar tip is significantly shorter in the retrognathic group, and accordingly, the position of the mandibular foramen is higher in the retrognathic group than that in the normal group.…”
Section: Considerations To Avoid Failure Of Conventional Ianbmentioning
confidence: 99%
See 2 more Smart Citations
“…For successful IANB, extraoral landmarks, such as degree of ramal flaring and height and width of the mandibular ramus as well as intraoral landmarks should be considered [1740]. You et al reported that the IANB failure rates were significantly higher in the retrognathic mandible (14.5%) than in the normal mandible (7.3%) and prognathic mandible (9.5%) [41]. It is because the distance from the mandibular foramen to the condylar tip is significantly shorter in the retrognathic group, and accordingly, the position of the mandibular foramen is higher in the retrognathic group than that in the normal group.…”
Section: Considerations To Avoid Failure Of Conventional Ianbmentioning
confidence: 99%
“…In contrast, since the mandibular foramen is located lower in patients with prognathic mandibles than that in the normal group, anesthetic solution can be infused superior to the mandibular foramen. In addition, sufficient mouth opening enables easy identification of anatomical structures [41]. Keros et al also reported that the location of the mandibular foramen was lower in patients with successful IANB [42].…”
Section: Considerations To Avoid Failure Of Conventional Ianbmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that this may be related to the relatively shorter condylar length in patients with a retrognathic mandible, in which case the position of the mandibular foramen is higher than in normal mandibles. If the anesthetic is injected at a higher point than normal in patients with retrognathic mandibles, the success rate of anesthesia may be increased [ 29 ]. Although the Gow-Gates technique has a higher success rate than the conventional technique and does not require an additional insertion for buccal nerve anesthesia, the delayed onset of action and difficulty of mastering the technique have been pointed out as its limitations [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inferior alveolar nerve block is a commonly performed procedure in the field of dentistry. It requires accurate identification of the anatomical location of the mandibular foramen, which varies among patients [ 7 ]. We are now capable of obtaining greater information about the mandibular foramen through 3D reconstruction of available CT images [ 8 ].…”
Section: Discussionmentioning
confidence: 99%